Gordonia asplenii sp. nov., isolated from humic soil on bird's nest fern (Asplenium nidus L.). Issue 3 (12th March 2021) - Suriyachadkun, Chanwit; Ngaemthao, Wipaporn; Pujchakarn, Tawanmol; Chunhametha, Suwanee
Abstract : A novel member of the actinobacteria, designated strain A-T 0013 T, was isolated from humic soil on a bird's nest fern ( Asplenium nidus L.) collected from Khao Yai National Park in Thailand. According the results of a polyphasic taxonomic study, A-T 0013 T had characteristics typical of members of the genus Gordonia . The 16S rRNA gene sequence indicated that A-T 0013 T shared ≤98 % sequence similarity with all members of the genus Gordonia . The most closely related species was Gordonia effusa IFM 10200 T (97.92 % sequence similarity). The average nucleotide identity based on blast (ANIb) value with G. effusa IFM 10200 T was 76.81 %. The cell-wall peptidoglycan contained meso -diaminopimelic acid. The whole-cell sugars contained ribose, arabinose and galactose. The predominant menaquinone was MK-9(H2 ). The predominant fatty acids were C16 : 0, C18 : 1 ω9 c, summed feature 3 (C16 : 1 ω7 c /C16 : 1 ω6 c ), and C18 : 0 10-methyl. Mycolic acid was present. The polar lipid profile for this strain ncluded diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylinositol and phosphatidylinositol mannosides. The G+C content of the genomic DNA was 66.1 mol%. Differentiation of A-T 0013 T from the most closely related species, Gordonia effusa IFM 10200 T, was evident from digital DNA–DNA hybridization values of 21.8 %. On the basis of the results of comparative analysis of phenotypic, chemotaxonomic and genotypic data, strain A-T 0013 T is concluded to represent a novel species of the genus Gordonia, for which the name Gordonia asplenii sp. nov. is proposed. The type strain is A-T 0013 T (=TBRC 11910 T =NBRC 114549 T ).